Proteomic response of Escherichia coli to the alkaloid extract of Papaver polychaetum - SARIYAR AKBULUT, BERNA; KAZAN, DİLEK (SPRINGER, 2010)
The cellular response of Escherichia coli exposed to alkaloids extracted from a biennial endemic plant, Papaver polychaetum, was explored using proteome analysis. Following determination of the minimum inhibitory concentration of the berberine-containing plant extract as 1,250 mu g/mL, E. coli cells were grown in the presence of 750 mu g/mL extract. The response of the bacteria to the extract, with berberine found as the major alkaloid, was analyzed on two-dimensional gels. The differentially expressed proteins in the presence of 750 mu g/mL extract were identified by matrix-assisted laser desorption/ionization-time of flight mass spectrometry. These proteins included those that play vital roles for maintenance such as protein synthesis (elongation factor-Ts), transport (oligopeptide-binding protein A, uncharacterized amino-acid ABC transporter ATP binding protein YECC), energy metabolism (alpha-subunit of ATP synthase, pyridine nucleotide transhydrogenase STHA) and regulation. These results provide clues for understanding the mechanism of the alkaloid extract-induced stress and cytotoxicity on E. coli. The altered proteins can serve as potential targets for development of innovative therapeutic agents.
Keywords: Proteomics; Antimicrobial; Escherichia coli; Papaver polychaetum; Berberine; ANTIMICROBIAL ACTIVITY; BINDING PROTEIN; BERBERINE; DNA; EXPRESSION; GENE; CLEAVAGE; GENOME; MODE